THE EFFECT OF PERCEIVED QUALITY, PERCEIVED SACRIFICE, AND PERCEIVED VALUE ON SATISFACTION WINZA FASHION BOUTIQUE CUSTOMERS (CASE STUDY OF WINZA FASHION BOUTIQUE CUSTOMERS IN DELITUA DISTRICT) - Amelia; Arief Hardian; Rukmini; Melisa Zuriani Hasibuan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the impact of perceived quality, perceived sacrifice, and perceived value on customer satisfaction at Winza Fashion Boutique in Delitua. Using a quantitative approach with an associative approach, 96 respondents were selected using the Lemeshow formula . The research instrument has been determined to be reliable and valid based on Cronbach's Alpha (>0.6 ) and validity checks. The results of multiple regression analysis indicate that the independent variables have a positive and significant impact on customer satisfaction, both directly and indirectly. The t-test shows that each variable is significant with a sig <0.05 , while the F-test produces an F-count of 4.317 which is greater than the F-table of 2.704 with a significance of 0.013. The coefficient of determination (R²) of 0.826 indicates that 82.6% of the variation in participant performance can be explained by the independent variables, while the remaining 17.4% is caused by factors outside the study.